Effectiveness of a dry-land resistance training program on strength, power, and swimming performance in paralympic swimmers - Dingley, A. A.; Pyne, D. B.; Youngson, J.; Burkett, B. (The Journal of Strength and Conditioning Research, 2015)
This study evaluated the effectiveness of a dry-land resistance training program in Paralympic swimmers to increase swimming power and strength measures, and how these changes affect swimming performance. Seven elite-level Paralympic swimmers (1 man and 6 women; age: 19.4 ± 6.5 years; body mass: 57 ± 12 kg; height: 1.66 ± 0.21 m) performed a 6-week coach-prescribed strength training intervention program designed to improve power, flexibility, and postural control. Exercises targeted the main swimming movements: the start and turn, postural control in the water, and the pull and kick focusing on the gluteals, upper body, and trunk. Swimming-specific tests, involving a 50-m time trial, and timed dive starts were conducted at baseline and after the 6-week program. A bilateral swim-bench ergometer and jump tests were conducted to quantify arm and leg strength and power. After the 6-week intervention, 50-m time trials improved by 1.2%, ±1.5% (mean, ±90% confidence limits). Increases in both mean power (6.1%, ±5.9%) and acceleration (3.7%, ±3.7%) generated during the dive start enabled swimmers to substantially improve start times to the 5-m (5.5%, ±3.2) and 15-m (1.8%, ±1.1%) marks. The resistance training intervention resulted in a very large (r = 0.78, ±0.37) correlation between dive start velocity and the counter movement jump mean velocity. The 6-week resistance training program for Paralympic swimmers yielded substantial improvements in dry-land measures that corresponded with improvements in both timed dive starts and 50-m time trial performance, thus highlighting the usefulness of dry-land training for enhancing swimming performance in Paralympic swimming.